CONSISTENT MODELING OF THE XRD PATTERNS OF MIXED-LAYER PHYLLOSILICATES - Plançon A. (My University, 2004)
The Markovian model of mixed-layering that has been used until now for the modeling of X-ray diffraction (XRD) patterns of 2:1 phyllosilicates describes the mixed-layer crystals as stacks of 'layer units' (LUs) that associate a 2:1 layer with an interlayer content. This model is not consistent when it is applied to a mixed-layer mineral (MLM) involving electrically charged layers, i.e . most of the mixedlayer phyllosilicates with 2:1 layers. Two consistent models can be proposed for these MLMs, which, instead of LUs, stack 'interlayer units' (IUs), composed of an interlayer content sandwiched between two half-layers. The IU-NPL model (interlayer units, non-polar layers) imposes non-polarity on the 2:1 layers resulting from the stack of these IUs, which implies restrictions on the succession of the IUs. In the other consistent model, the IU-PL one (interlayer units, polar layers), these restrictions are not imposed. These two models reproduce the Non-Polar 2:1 Layer Model and the Polar 2:1 Layer Model described by Altaner and Ylagan for illite-smectite mixed layering, and the second model corresponds to the stacks of O0.5 T I' T O0.5 units described by Olives et al. The present work points out the similarities and discrepancies of the calculated XRD patterns by using computer programs designed for the three models of mixed-layering (LU, IU-NPL and IU-PL) and for twoand three-component MLMs. Illustrations are provided for some I-S and I-S-V MLMs. The IU-PL model leads to XRD patterns similar to those of the LU model. It is in agreement with latticeenergy calculations, expandability measurement, HRTEM imaging and NMR spectroscopy.